2017
DOI: 10.7554/elife.26693
|View full text |Cite
|
Sign up to set email alerts
|

MELK is not necessary for the proliferation of basal-like breast cancer cells

Abstract: Thorough preclinical target validation is essential for the success of drug discovery efforts. In this study, we combined chemical and genetic perturbants, including the development of a novel selective maternal embryonic leucine zipper kinase (MELK) inhibitor HTH-01-091, CRISPR/Cas9-mediated MELK knockout, a novel chemical-induced protein degradation strategy, RNA interference and CRISPR interference to validate MELK as a therapeutic target in basal-like breast cancers (BBC). In common culture conditions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 57 publications
8
90
3
Order By: Relevance
“…We used an inducible degradation system (Erb et al, 2017; Huang et al, 2017; Winter et al, 2015) to fully deplete YY1 protein levels and measured the impact on gene expression in mESCs genome-wide through RNA sequencing (RNA-seq) analysis (Figures 5A and 5B). Depletion of YY1 led to significant (adjusted p value <0.05) changes in expression of 8,234 genes, divided almost equally between genes with increased expression and genes with decreased expression (Figure 5C; Table S2; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…We used an inducible degradation system (Erb et al, 2017; Huang et al, 2017; Winter et al, 2015) to fully deplete YY1 protein levels and measured the impact on gene expression in mESCs genome-wide through RNA sequencing (RNA-seq) analysis (Figures 5A and 5B). Depletion of YY1 led to significant (adjusted p value <0.05) changes in expression of 8,234 genes, divided almost equally between genes with increased expression and genes with decreased expression (Figure 5C; Table S2; Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we demonstrated that the MELK inhibitor OTS167 remained effective against MELK-mutant cells, suggesting that OTS167 kills cells through an off-target mechanism. These results have been replicated by an independent group, who further demonstrated that the shRNA vectors commonly used to study MELK also kill cells in a MELKindependent manner (16). The off-target effects of both the small-molecule MELK inhibitor and the MELK-targeting shRNAs provide a potential explanation for certain previous results obtained studying this potential drug target.…”
Section: Introductionmentioning
confidence: 63%
“…Although all MELK-KO cells grow well when seeded at high density in proliferation assays (15, 16), plating cells at low density can challenge a cell's colony-forming ability and replicative lifespan (35). To test whether MELK loss confers a defect in colony growth, MELK-KO and Rosa26 DLD1, A375, Cal51, and MDA-MB-231 clones were serially-diluted and allowed to grow at varying cell densities.…”
Section: Melk Is Dispensable For Growth In Vitro and In Vivomentioning
confidence: 99%
See 2 more Smart Citations